(untitled) (American Journal of Islam and Society, 1994)
llris seminar was the second in a series of seminars held jointly by the International Institute of Islamic Thought (IIIT) in cooperation with the Kuwaiti Department of Awqaf. The inaugural session of the seminar was addressed by the Minister for Awqaf and Islamic Affairs, Jam’an al ’Azimi, who stated that the topic of the seminar sufficed to indicate its importance. The following speaker, the Secretary of the Ministry, Khalid al Zir, underlined the fact that while everyone agreed on the need to return to the pristine teachings of the Qur’an and the Sunnah, it was not an easy matter to determine how, in practical tenns, this might be achieved. This is why, the Secretary said, this seminar was convened. Taha Jabir al ’Alwani, President of the International Institute of Islamic Thought, after making his opening remarks, delivered a paper entitled The Horizons of Change and Its Approaches, in which he stated that the Arab world had very recently reached a critical stage. Many analytical studies of various aspects of the Arab situation, he added, had been conducted from several different perspectives. Undoubtedly, on the basis of these studies, the outlines of an alternative civilizational project may emerge. It is for this reason that the topic of the seminar, "Methodologies of Change in the Contemporary Islamic World," is of such overwhelming importance. Muhammad al Ghazali, the noted Muslim ’alim and author, then spoke on behalf of the seminar participants. Prefacing his remarks by noting the importance of Kuwait in the Arab and Muslim worlds, al Ghazali explained that it is the duty of Muslims everywhere to work together to further the cause of Islam. This is why, he added, the cooperation of the Kuwaiti Ministry with the International Institute of Islamic Thought was such a commendable undertaking. The seminar was comprised of four distinctive themes. The first one dealt with defining the concept of change within the Islamic paradigm, beginning with the Qur’an, the Sunnah, and the historical experience of Islam. This concept may be studied in light of the theories and opinions of the classical scholars of Islam. In addition, it may prove beneficial to study it in conjunction with such similar concepts within the Islamic paradigm as tajdid, reform, revival, awakening, revolution, modernization, development, and progress. Topics for discussion included the following: ...